2019
DOI: 10.1177/1941738119885642
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Anterior Cruciate Ligament Injury in Italian First Division Soccer Players

Abstract: Background: The burden of anterior cruciate ligament (ACL) injury in professional soccer players is particularly relevant as it represents a potentially career-threatening injury. Hypothesis: Our hypotheses were that (1) injury incidence rate would be similar to that reported in the literature, (2) we would identify a uniform distribution of the injuries along the season, and (3) injury incidence rate would be similar in high-ranked and lower ranked teams, based on final placement in the league. Study Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 43 publications
3
36
1
1
Order By: Relevance
“…A study by Alberto Grassi, published in Sport Health in 2019. 24 showed 0.421 injuries per 1,000 hours played in the first division of the Italian championship, and Waldén et al 12 obtained slightly lower results than those found in our study (0.309 injuries), in the main European leagues, which can still be considered close. We notice a big difference when analyzing the incidences of injury in the first and second divisions of the Brazilian championship separately.…”
Section: Discussioncontrasting
confidence: 67%
“…A study by Alberto Grassi, published in Sport Health in 2019. 24 showed 0.421 injuries per 1,000 hours played in the first division of the Italian championship, and Waldén et al 12 obtained slightly lower results than those found in our study (0.309 injuries), in the main European leagues, which can still be considered close. We notice a big difference when analyzing the incidences of injury in the first and second divisions of the Brazilian championship separately.…”
Section: Discussioncontrasting
confidence: 67%
“…To determine the performance of structured training, identify relationships between indicators of physiological function and performance of physical and technical preparedness correlation analysis was conducted performance testing of athletes control Health, sport, rehabilitation Здоров'я, спорт, реабілітація Здоровье, спорт, реабилитация 7(1) and experimental groups before and after the experiment (Table. [5][6][7][8]. Prior to the experiment, the number of reliable relationships between psychophysiological indicators and indicators of physical and technical preparedness in both the control and experimental groups was 5-6 interconnections (Table 5, 6).…”
Section: Resultsmentioning
confidence: 99%
“…Complex development of punches accuracy, strength, speed, endurance, agility is also effective for preventing injuries and diseases of football players [7][8][9][10][11][12], for increasing the functional capabilities of vegetative-vascular regulation [13]. The authors of [14] revealed the influence of body size on the effectiveness of the game of football players from different regions and showed that the accuracy of strikes in football is a complex psychomotor function that depends on the morphological characteristics of the players, which determines the development of physical qualities [15].…”
Section: Introductionmentioning
confidence: 99%
“…Among different tendon and ligament, Achilles tendon ( Raikin et al, 2013 ), anterior cruciate ligament ( Grassi et al, 2020 ) and rotator cuff ( Tashjian, 2012 ) showed prominently higher incidents of rupture, which aroused wide interests in the repair of these tissues. And these three kinds of tendon and ligament are particularly important for the body to maintain normal physiological function, it is necessary to choose the appropriate treatment to repair the tendon and ligament to the maximum extent ( Figure 2A ).…”
Section: Introductionmentioning
confidence: 99%